Pengaruh Efisiensi Operasional, Audit Tenure dan Financial Distress terhadap Audit Report Lag dengan Size Company sebagai Variabel Moderasi: Studi Empiris pada Perusahaan Subsektor Properti dan Real Estate yang Terdaftar di BEI Tahun 2022-2024 - Finanta Fiarcio; Einde Evana (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
Audit tenure, and financial distress in the audit report lag of companies in the property and real estate subsector listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. Operational efficiency is then measured using the BOPO ratio. Audit tenure is measured by assigning a score of 1 if the company’s auditor is consistent and adding +1 whenever each year continues and returning 0 if there is a replacement auditor. Financial distress is then calculated using the Grover model, and audit report lag is calculated based on the difference in days between the audit report date and the financial statements. Company size is measured by Ln (Total Assets). Furthermore, the method used in this study is quantitative with a purposive sampling technique analyzed using multiple linear regression and moderated regression analysis. Operational efficiency hazards have a positive and significant effect on audit report lag, meaning that in this case the BOPO ratio has a high probability of being related to delays in longer audit reports. Audit tenure does not have an effect on audit report lag. Furthermore, financial distress has a negative and significant effect, indicating that companies experiencing lower financial difficulties tend to have a shorter audit report lag. Company size strengthens the influence of operational efficiency on audit report lag. Company size also does not moderate the relationship between audit tenure and report lag. Company size weakens the effect of financial distress on audit report delays. These findings demonstrate the importance of maintaining timely audit reporting for investors in decision-making. This study contributes to the literature on auditors and future research.